2013
DOI: 10.5114/fn.2013.39718
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Purkinje cell vulnerability to prenatal nicotine exposure in sudden unexplained perinatal death

Abstract: A b s t r a c tThe present study was aimed at supplementing our previous investigations on the morphological

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
3
20
0
1
Order By: Relevance
“…Our previous studies have reported on an array of important side effects of nicotine exposure on the developmental process of the different brainstem centers essential for life (Lavezzi, Ottaviani, Mingrone, et al., 2005; Lavezzi, Ottaviani, Matturri, 2005; Lavezzi et al., 2007; Lavezzi et al., 2013; Lavezzi, Ferrero, et al., 2016). The findings of our study add new insights to this field and highlight the fact that the altered expression of nAChR, also limited to CC, puts fetuses exposed to maternal cigarette smoking in utero, at higher risk of SIDS or SIUDS.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have reported on an array of important side effects of nicotine exposure on the developmental process of the different brainstem centers essential for life (Lavezzi, Ottaviani, Mingrone, et al., 2005; Lavezzi, Ottaviani, Matturri, 2005; Lavezzi et al., 2007; Lavezzi et al., 2013; Lavezzi, Ferrero, et al., 2016). The findings of our study add new insights to this field and highlight the fact that the altered expression of nAChR, also limited to CC, puts fetuses exposed to maternal cigarette smoking in utero, at higher risk of SIDS or SIUDS.…”
Section: Discussionmentioning
confidence: 99%
“…The high metabolic rate may contribute to cerebellar vulnerability to mitochondrial dysfunction, RNA toxicity, environmental insults, and comorbidity, and thus increase its risk of atrophy during aging. Indeed, intranuclear inclusions have been observed in dentate nuclei, reflecting the effect of RNA toxicity; and mitochondrial dysfunction (Ross-Inta et al , 2010, Napoli et al , 2016) and high prevalence of hypertension, substance abuse and alcohol abuse have been reported in premutation carriers (Dorn et al , 1994, Kogan et al , 2008, Polussa et al , 2014), which may play a role in cerebellar atrophy during aging (Miquel et al , 2009, Lavezzi et al , 2013, Miquel et al , 2016). Additional studies are needed to uncover the mechanisms causing cerebellar underdevelopment often with specific developmental problems and late neurodegeneration due to FXTAS progression.…”
Section: Discussionmentioning
confidence: 99%
“…This study was, however, limited to the brainstem examination. Therefore, here our aim was to extend our previous investigation by focusing, in the same cases, on the BDNF expression in the cerebellum and, above all, in cerebellar cortex, which we have already shown to be particularly susceptible to developmental abnormalities in sudden perinatal death victims, especially in association with risk factors such as exposure to cigarette smoke (Lavezzi et al, 2006a; Lavezzi et al, 2013; Lavezzi et al, 2006b; Lavezzi et al, 2007; Lavezzi et al, 2016).…”
Section: Introductionmentioning
confidence: 97%